The value of the prooxidant-antioxidant system in ensuring the immunity of plants - Bobrova, Mariia; Holodaieva, Olena; Arkushyna, Hanna; Larycheva, Olena; Tsviakh, Olha (Revista de la Universidad del Zulia, 2020)
Aim of the research: to identify changes in the state of the prooxidant-antioxidant system in the organs of different plant varieties, depending on their level of resistance to disease. The subject of the research is the role of individual components of the prooxidant-antioxidant system in ensuring plant resistance to disease. Methodology. Quantitative determination of PAS status was performed on onion tissue samples taken from the following varieties: "Globus" (high-resistant variety), "Rainbow" (medium-resistant variety) and "Donetsk Golden" ( low-resistant variety). For biochemical analysis, tissues from the top of the leaf, the middle of the leaf, the scales of the onion-turnip, stem, flower, roots, and seeds were used. The concentration of superoxide anion radical, TBA-active products, superoxide dismutase activity, catalase, GSH-peroxidase, the concentration of ascorbic acid, glutathione, cytochrome oxidase activity were determined. The results of the research show that іn the tissues of photosynthetic vegetative organs of onions, there is an increase in both parts of the prooxidant-antioxidant system; in tissues that are not capable of photoproduction, there is an advantage of the antioxidant link in accordance with the increased resistance of the variety to disease. Initiation of germination processes enhances the activity of both parts of the prooxidant-antioxidant system and is highest in flower cells. Onion seed tissues, which are at rest, have the advantage of a prooxidant link and an increase in the concentration of low molecular weight antioxidants. Practical consequences. As a result of the correlation analysis of the studied indicators, the presence of a close relationship between the concentration of TBA-active products and the activity of cytochrome oxidase and superoxide dismutase,  ascorbate with glutathione was established.